COVID-19 is a multi-organ aggressor: epigenetic and clinical marks - Kgatle, MM; Lawal, I; Mashabela, G; Boshomane, T; Koatale, P; Mahasha, P; Ndlovu, H; Vorster, M; Rodrigues, H; Zeevaart, J; Gordon, S; Moura Alves, P; et al. (Frontiers Media, 2021)
The progression of coronavirus disease 2019 (COVID-19), resulting from a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, may be influenced by both genetic and environmental factors. Several viruses hijack the host genome machinery for their own advantage and survival, and similar phenomena might occur upon SARS-CoV-2 infection. Severe cases of COVID-19 may be driven by metabolic and epigenetic driven mechanisms, including DNA methylation and histone/chromatin alterations. These epigenetic phenomena may respond to enhanced viral replication and mediate persistent long-term infection and clinical phenotypes associated with severe COVID-19 cases and fatalities. Understanding the epigenetic events involved, and their clinical significance, may provide novel insights valuable for the therapeutic control and management of the COVID-19 pandemic. This review highlights different epigenetic marks potentially associated with COVID-19 development, clinical manifestation, and progression.